Natural food mastication capability in preschool children according to their oral condition: A preliminary study - Linas, Natacha; Peyron, Marie‐Agnès; Eschevins, Caroline; Hennequin, Martine; Nicolas, Emmanuel; Collado, Valérie (Journal of texture studies, 2020)
This study investigated, for the first time, the masticatory capability of preschool children using natural foods, and the impact of an early oral health alteration (early childhood caries: ECC) on the granulometry of ready‐to‐swallow food boluses. Thirteen children with ECC were compared to 13 preschool children with a healthy oral condition. Oral health criteria and NOT‐S scores (Nordic Orofacial dysfunction Test‐Screening) were recorded. For each child, number of masticatory cycles (Nc), chewing time (Ti), and frequency (Fq = Nc/Ti) were recorded during mastication of raw carrot (CAR), cheese (CHS) and breakfast cereals (CER) samples. Food boluses were collected by stopping children at their food‐dependent individual swallowing threshold (Nc), and the median food bolus particle size value (D50) was calculated. Correlations were sought between oral health and masticatory criteria. In the ECC group, mean Fq values were significantly decreased for all three foods (p ≤ .001) and mean D50 values were significantly increased (p ≤ .001) compared to the control group (i.e., D50 CAR = 4,384 μm ± 929 vs. 2,960 μm ± 627). These alterations were related to the extent of ECC. The NOT‐S mean global score was significantly increased in children with ECC (2.62 ± 1.37 vs. 1 ± 0.91 in the control group, p ≤ .01), due to “Mastication and swallowing” domain impairment. This study gives granulometric normative values for three foods in preschool children and shows the impact of ECC on D50 values. The progression of children's masticatory capability after dental treatment, and the impact of such modifications of sensory input on future eating habits should be explored.